Role of Microfinance and Financial Inclusion in the Development of Indian Farmers: A Quantitative Investigation - BHARDWAJ, RAJNEESH (International Journal of Psychosocial Rehabilitation, 2024)
A country’s economiSc rural and urban segments equally rely on the agricultural industry since it creates jobs in the former and supplies nourishment and unprocessed goods to the later. In addition to its critical contribution to the course of global growth, money plays a significant role in the constraints faced by peasants in emerging nations. The production of the agriculture land is adversely impacted by the lack of enough financing when it is required. Gross domestic product (GDP) of a nation suffers significantly when people are denied access to fundamental banking services. Authorities are proactive and occasionally launch a number of policy initiatives to ameliorate the position of such growers because marginal and small-scale farmers predominate the agricultural industry in these nations. However, the bulk of these people don’t have quick access to the credit facilities they have to complete their output.